THE INFLUENCE OF DIGITAL MARKETING, SOCIAL MEDIA INFLUENCERS, AND DISCOUNTS ON PURCHASE INTENTION OF FASHION PRODUCTS ON THE TIKTOK SHOP PLATFORM AMONG GENERATION Z STUDENTS OF THE FACULTY OF ECONOMICS AND BUSINESS, MALIKUSSALEH UNIVERSITY - Ikramuddin; Leli Anita; Khairina AR; T. Edyansyah (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to determine the effect of digital marketing, social media influencers, and discounts on purchase intentions for fashion products on the TikTok Shop platform among Generation Z, especially students of the Faculty of Economics and Business, Malikussaleh University. The increasing trend of online shopping among the digital generation has encouraged the need to understand the factors that influence consumer decisions in shopping, especially on rapidly growing social media platforms such as TikTok Shop. This study uses a quantitative approach with a survey method by distributing questionnaires to 108 respondents selected by purposive sampling. Data were analyzed using multiple linear regression to test the effect of each independent variable on the dependent variable. The results showed that the three variables, namely digital marketing, social media influencers, and discounts, have a positive and significant effect on purchase intentions for fashion products on TikTok Shop. Digital marketing facilitates access to product information, influencers play a role in forming positive perceptions, and discounts attract consumers' interest in making purchases. The implications of this study provide insight for fashion entrepreneurs and digital marketers to design effective marketing strategies in attracting Gen Z consumers' buying interest through social media, especially TikTok.